Prevalence and pattern of disclosure of HIV status in HIV-infected children in Ghana. - Kallem, Stacey; Renner, Lorna; Ghebremichael, Musie; Paintsil, Elijah (AIDS and behavior, 2011)
With the advent of highly active antiretroviral therapy (HAART) HIV-infected children are surviving into adulthood. Despite emerging evidence of the benefits of disclosure, when and how to disclose the diagnosis of HIV to children remain a clinical dilemma. We investigated the prevalence and determinants of HIV disclosure in a cross-sectional study of 71 caregiver-child dyads from the Pediatric HIV/AIDS Care Program at Korle-Bu Teaching Hospital (Accra, Ghana). The children were between 8 and 14 years of age (median age, 10.39 years). The prevalence of disclosure was 21%. In the unadjusted analyses, the age of child, the level of education of child, deceased biologic father, administration of own HIV medications, and longer duration on HIV medication were significantly associated with disclosure. The low prevalence of disclosure underscores the need for a systematic and a staged approach in disclosing HIV status to infected children in resource limited countries.
Keywords: Adolescent; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Caregivers; Child; Cross-Sectional Studies; Family Characteristics; Female; Ghana; HIV Infections; HIV-1; Hospitals, Teaching; Humans; Male; Prevalence; Truth Disclosure